Regulatory Network of Cotton Genes in Response to Salt, Drought and Wilt Diseases (Verticillium and Fusarium): Progress and Perspective - Billah, Masum; Li, Fuguang; Yang, Zhaoen (Frontiers in Plant Science, 2021)
In environmental conditions, crop plants are extremely affected by multiple abiotic stresses including salinity, drought, cold, and heat, as well as several biotic stresses such as pests and pathogens. However, salinity, drought, and wilt diseases (e.g., Fusarium and Verticillium) are considered the most destructive environmental stresses to cotton plants. These cause severe growth interruption and yield loss of cotton. Since cotton crops are central contributors to total worldwide fibre production, and also important for oilseed crops, it is essential to improve stress tolerant cultivars to secure future sustainable crop production under adverse environments. Plants have evolved complex mechanisms to respond and acclimate to adverse stress conditions at both physiological and molecular levels. Recent advances in molecular genetics have delivered new insights into the regulatory network system of plant genes, which generally includes defence of cell membranes and proteins, signalling cascades and transcriptional control, and ion uptake and transport and their relevant biochemical pathways and signal factors. In this review, we mainly summarize recent progress concerning several resistance-related genes of cotton plants in response to abiotic (salt and drought) and biotic (Fusarium and Verticillium wilt) stresses and classify them according to their molecular functions to better understand the genetic network. Moreover, this review proposes that studies of stress related genes will advance the security of cotton yield and production under a changing climate and that these genes should be incorporated in the development of cotton tolerant to salt, drought, and fungal wilt diseases (Verticillium and Fusarium).